EFFECTIVENESS OF GROUP WORK USING POSITIVE REINFORCEMENT TO REDUCE OFF-TASK BEHAVIOR IN GRADE XI STUDENTS - Nurhanifah, Utari; Maghfiroh, Nasruliyah Hikmatul; Ulwiyah, Imaratul; Sayyidulhaq, Salman (Jurnal Bikotetik (Bimbingan dan Konseling: Teori dan Praktik), 2025)
The purpose of this study is to determine the effectiveness of the positive reinforcement technique in overcoming students' off-task behavior, off-task problems become an obstacle in the implementation of learning in schools. Student off-task behavior is behavior that comes out of learning activities in the classroom such as talking to friends, sleeping, disturbing friends, daydreaming and so on, of course this behavior can be detrimental to individuals and groups, namely it can interfere with the learning process in the classroom in the form of decreased focus and interest of students in learning so that it causes academic grades and achievements to decrease and are not in accordance with educational targets and goals. In this study, the method used is quantitative pre-experimental desaign, with a one-group pretest-posttest desaign research design. In the design of this study, a pre-test will be carried out before being treated with a positive reinforcement technique, so that the results of the treatment can be known more accurately because the results of the post-test can be compared with the state before the treatment was given